Chương I - Căn bậc hai. Căn bậc ba

HD

Cho \(\left(x+\sqrt{x^2+2003}\right)\cdot\left(y+\sqrt{y^2+2003}\right)=2003\)

Tính x+y?

XT
25 tháng 7 2017 lúc 21:55

Ta có:\(\left(x+\sqrt{x^2+2003}\right)\left(y+\sqrt{y^2+2003}\right)=\dfrac{\left(x+\sqrt{x^2+2003}\right)\left(x-\sqrt{x^2+2003}\right)\left(y+\sqrt{y^2+2003}\right)\left(y-\sqrt{y^2+2003}\right)}{\left(x-\sqrt{x^2+2003}\right)\left(y-\sqrt{y^2+2003}\right)}=\dfrac{\left(x^2-x^2-2003\right)\left(y^2-y^2-2003\right)}{\left(x-\sqrt{x^2+2003}\right)\left(y-\sqrt{y^2+2003}\right)}=\dfrac{2003^2}{\left(x-\sqrt{x^2+2003}\right)\left(y-\sqrt{y^2+2003}\right)}=2003\)

=>\(\left(x-\sqrt{x^2+2003}\right)\left(y-\sqrt{y^2+2003}\right)=2003\)

=>\(\left(x-\sqrt{x^2+2003}\right)\left(y-\sqrt{y^2+2003}\right)=\left(x+\sqrt{x^2+2003}\right)\left(y+\sqrt{y^2+2003}\right)\)

nhân phá và thu gọn ta được

\(x\sqrt{y^2+2003}=-y\sqrt{x^2+2003}\)(1)

Bình phương

=>x2y2+2003x2=x2y2+2003y2

<=>x2=y2

<=>x=y hoặc x=-y

Thay vào (1) thì

x=y <=>x=y=0

x=-y (luôn đúng)

=>x+y=0

Bình luận (0)